Asymmetric Allylic C–H Oxidation for the Synthesis of Chromans - Wang, Pu-Sheng; Liu, Peng; Zhai, Yu-Jia; Lin, Hua-Chen; Han, Zhi-Yong; Gong, Liu-Zhu (Journal of the American Chemical Society, 2015)
An enantioselective intramolecular allylic C–H oxidation to generate optically active chromans has been accomplished under the cooperative catalysis of a palladium complex of chiral phosphoramidite ligand and 2-fluorobenzoic acid. Mechanistic studies suggest that this reaction commences with a Pd-catalyzed allylic C–H activation event and then undergoes asymmetric allylic alkoxylation. The synthetic significance of the method has been embodied by concisely building up a key chiral intermediate to access (+)-diversonol.